2008
DOI: 10.1103/physrevb.77.033406
|View full text |Cite
|
Sign up to set email alerts
|

Exciton dephasing and multiexciton recombinations in a single carbon nanotube

Abstract: We studied the temperature and excitation intensity dependence of exciton luminescence in individual single-walled carbon nanotubes (SWNTs) using single

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
135
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(144 citation statements)
references
References 32 publications
7
135
1
Order By: Relevance
“…Although phonon-induced broadening was experimentally investigated by means of various techniques for SWNTs of different diameters [13,[16][17][18]20], there is so far no theoretical calculation of the exciton-phonon coupling efficiency in these 1D systems. In order to provide a quantitative interpretation of our measurements, we have calculated the temperature-dependence of the excitonic homogeneous linewidth due to the interaction with acoustic phonons.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Although phonon-induced broadening was experimentally investigated by means of various techniques for SWNTs of different diameters [13,[16][17][18]20], there is so far no theoretical calculation of the exciton-phonon coupling efficiency in these 1D systems. In order to provide a quantitative interpretation of our measurements, we have calculated the temperature-dependence of the excitonic homogeneous linewidth due to the interaction with acoustic phonons.…”
Section: Figmentioning
confidence: 99%
“…where Γ 0 is the residual homogeneous linewidth in the limit of zero temperature (in the range of several meVs [13,[16][17][18]), aT the broadening due to low-energy acoustic phonons, and b exp [18]. In our case, the fit displayed as solid red line in Fig.2 is obtained by taking Γ 0 =6.9±0.2 meV, and a=32±3 µeV.K −1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature dependencies of the transition rate or energy broadening for excitons near band edges are monotonically increasing functions, which have been attributed to scattering from acoustic phonons around the point and analyzed by using linear functions, sometimes plus the Bose-Einstein distribution with a constant phonon frequency. [24][25][26][27] Recent experiments on the exciton-acousticphonon scattering using nanotubes with an almost unique chirality 24 or single isolated nanotubes 25,26 are suitable to quantitative comparison between experiments and theories.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many theoretical studies on this subject have been reported which include, for example, excitons trapped by impurity potentials, 15,16 phonon side bands for exciton peaks in optical spectra, 17 the interaction of excitons with acoustic and optical phonons in zigzag nanotubes, 18 and the chirality dependence of the Raman scattering intensity for the breathing-mode phonons. 19,20 Experimentally, transition rates, [21][22][23][24] the linewidth of exciton peaks, [25][26][27] and diffusion constants and diffusion lengths [28][29][30][31][32][33][34][35] have been intensively studied for excitons interacting with disorders and phonons in nanotubes. The results strongly depend on the experiments.…”
Section: Introductionmentioning
confidence: 99%